Genomics approaches to elucidate the evolution and population histories of Southeast Asian forest trees and their connection to biogeography: a case study of Fagraea sensu lato - Cho, Nicholas Rui Wen (Nanyang Technological University, 2023)
Southeast Asia (SEA) harbors exceptional species richness, but its forests are under anthropogenic threats, in a refugial state, and understudied. Parts of SEA are in the Indo-Australia Archipelago (IAA), which contains a quarter of all terrestrial species. Thus, we seek to establish Fagraea sensu lato and tembusu as models, species found widely across SEA, to observe how climate and sea level affects the population histories of SEA and IAA forests, by utilizing both bioinformatic tools and ecological techniques. The disputed phylogeny of Fagraea sensu lato is to be resolved and incomplete lineage sorting (ILS) examined in this genus. Effective population sizes are hypothesized to increase as climatically suitable area increases, and decrease as sea level increases; but the inverse was found for most samples, suggesting that local conditions or other factors are at play. In addition, a method was developed to detect ILS; and genes and genomic regions harboring ILS.